Translation Revision as Rereading: Different Aspects of the Translator’s and Reviser’s Approach to the Revision Process - Scocchera, Giovanna (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2017)
As a synonym for “revision,” dictionaries of different European languages include such terms as rilettura, relecture, relectura and rereading. The concept of “rereading” is also used by most translators and revisers when having to describe the process of revising a translation. This act of rereading, however, takes on different forms and purposes depending on the agent by whom it is performed, that is, the translator of the text or the reviser of the translation. As a matter of fact, revision is a second, further reading for the translator who has been working on his/her translation, but it is a “new” reading for the reviser, who approaches the translated text for the first time and, because of his/her “new vision,” can provide different insights on the work done by the translator and spot any weaknesses it may have. Drawing on current research in the field of revision as well as on first-hand data on professional revision in the publishing sector, this work aims at highlighting the peculiarities of revision as rereading when performed by translators and revisers as well as analyzing the latter’s different modes of execution, strategies, purposes and products.